Diffusion MRI detects early brain microstructure abnormalities in 2‐month‐old 3×Tg‐AD mice. (17th June 2020) - Falangola, Maria Fatima; Nie, Xingju; Ward, Ralph; McKinnon, Emilie T.; Dhiman, Siddhartha; Nietert, Paul J.; Helpern, Joseph A.; Jensen, Jens H.
Abstract : The 3×Tg‐AD mouse is one of the most studied animal models of Alzheimer's disease (AD), and develops both amyloid beta deposits and neurofibrillary tangles in a temporal and spatial pattern that is similar to human AD pathology. Additionally, abnormal myelination patterns with changes in oligodendrocyte and myelin marker expression are reported to be an early pathological feature in this model. Only few diffusion MRI (dMRI) studies have investigated white matter abnormalities in 3×Tg‐AD mice, with inconsistent results. Thus, the goal of this study was to investigate the sensitivity of dMRI to capture brain microstructural alterations in 2‐month‐old 3×Tg‐AD mice. In the fimbria, the fractional anisotropy (FA), kurtosis fractional anisotropy (KFA), and radial kurtosis ( K ┴ ) were found to be significantly lower in 3×Tg‐AD mice than in controls, while the mean diffusivity (MD) and radial diffusivity ( D ┴ ) were found to be elevated. In the fornix, K ┴ was lower for 3×Tg‐AD mice; in the dorsal hippocampus MD and D ┴ were elevated, as were FA, MD, and D ┴ in the ventral hippocampus. These results indicate, for the first time, dMRI changes associated with myelin abnormalities in young 3×Tg‐AD mice, before they develop AD pathology. Morphological quantification of myelin basic protein immunoreactivity in the fimbria was significantly lower in the 3×Tg‐AD mice compared with the age‐matched controls. Our results demonstrate that dMRI is able to detect widespread, significant early brain morphological abnormalities in 2‐month‐old 3×Tg‐AD mice. Abstract : In vivo diffusion MRI metrics are shown to be sensitive indicators of early changes in the integrity and complexity of the white matter (WM) microstructure in 2‐month‐old 3×Tg‐AD mice. Widespread significant WM abnormalities were detected and supported by histological (myelin basic protein immunohistochemistry) findings.